Institutionalizing Quality Culture in Non-Formal Islamic Education: Evidence from Qiroati-Based Qur’anic Schools in Indonesia - Mukhamad Saekan; Saim Kayadibi (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
This study examines the institutionalization of quality management in non-formal Islamic education at Qiroati-based Qur’anic schools in Indonesia, focusing on quality planning, implementation, evaluation, and institutional sustainability in community-based Islamic education. Recent discussions on educational quality assurance have highlighted the limited attention given to how quality management is culturally constructed and institutionally sustained within non-formal Islamic educational settings. Previous studies have primarily emphasized pedagogical effectiveness and Qur’anic learning outcomes, while the managerial and socio-cultural dimensions of quality management remain underexplored. Employing a qualitative ethnographic case study approach, data were collected through participant observation, in-depth interviews, and documentation involving institutional leaders, administrators, ustadz/ustadzah, and community stakeholders. Data were analyzed using Spradley’s ethnographic analytical framework, including domain, taxonomic, componential, and cultural theme analyses. The findings reveal that quality management is institutionalized through structured competency-based planning, standardized teacher development, participatory leadership, continuous evaluation, and value-based organizational culture rooted in Islamic ethics. Institutional sustainability is further strengthened by community trust, managerial commitment, and adaptive organizational practices, although challenges related to infrastructure limitations, time constraints for learning, and diverse student backgrounds persist. This study contributes theoretically by extending discussions on educational quality management beyond formal schooling frameworks into culturally grounded non-formal Islamic education contexts. Methodologically, it demonstrates the relevance of ethnographic analysis for understanding institutional culture and quality practices. In practical terms, the findings offer an adaptive framework for strengthening sustainable community-based Islamic educational institutions across broader Muslim societies.